1996
DOI: 10.2307/1131619
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Negative Affect in Parent-Child Interactions and Children's Peer Competency

Abstract: The relationship between preschool children's peer competency and the exchange of reciprocal negative affect displays during physical play with parents was examined. Teacher ratings of children's peer competency were obtained from children's preschools. Parents and children (41 families) were observed during a physical play paradigm called "the hand game" which permitted physically stimulating play, yet which also permitted clear recording of participants' facial expressions. Interactions were coded second by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 23 publications
9
127
2
3
Order By: Relevance
“…Other studies have shown that this form of play is associated with emotion-regulation [Barth and Parke, 1993;Carson and Parke, 1996] and emotion-encoding skills [Carson and Parke, 1996;Parke et al, 1988], both of which are known to be related to peer competence [Field and Walden, 2008;Zeman et al, 2006]. The most popular children are those of fathers who exhibit high levels of physical play with both sons and daughters (3-4 years) and elicit high levels of positive feelings during play sessions [Corr et al, 1995].…”
Section: Play and Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that this form of play is associated with emotion-regulation [Barth and Parke, 1993;Carson and Parke, 1996] and emotion-encoding skills [Carson and Parke, 1996;Parke et al, 1988], both of which are known to be related to peer competence [Field and Walden, 2008;Zeman et al, 2006]. The most popular children are those of fathers who exhibit high levels of physical play with both sons and daughters (3-4 years) and elicit high levels of positive feelings during play sessions [Corr et al, 1995].…”
Section: Play and Socializationmentioning
confidence: 99%
“…Fathers appear to socialize their children especially through physical play: father-child physical play is associated with peer competence [Carson and Parke, 1996;Lindsey et al, 1997;MacDonald and Parke, 1984]. Other studies have shown that this form of play is associated with emotion-regulation [Barth and Parke, 1993;Carson and Parke, 1996] and emotion-encoding skills [Carson and Parke, 1996;Parke et al, 1988], both of which are known to be related to peer competence [Field and Walden, 2008;Zeman et al, 2006].…”
Section: Play and Socializationmentioning
confidence: 99%
“…Parents and children can develop patterns of reciprocated emotional exchanges, such that as the parent's negativity increases, the child is more likely to react with increased negativity as well (Patterson, 1980). Carson and Parke (1996) found that reciprocal exchanges of negativity between parents and their children were correlated with negative social outcomes, suggesting that children who engaged in reciprocal negative exchanges with their parents were not well accepted by peers. Consistent with this perspective, Lindahl and Markman (1990) proposed that children growing up in families that have difficulty de-escalating negative emotions might have difficulties recognizing and managing their own negative emotion.…”
Section: Length Of Negative Emotion Exchangesmentioning
confidence: 99%
“…Given that differences exist between mothers and fathers in patterns of emotional expressiveness (Boyum & Parke, 1995) and verbal communication with children (Black & Logan, 1995), it is likely that the patterns of association between shared emotion and conversational equality observed for mother-child dyads will not be mirrored in father-child dyads. Additional research that examines dyadic synchrony in father-child relationships at multiple developmental periods is needed, given evidence that the quality of father-child interaction has unique consequences for children's adjustment (Carson & Parke, 1996). Finally, the measures used to assess early adolescent self-esteem and prosocial behavior were limited in that they contained a relatively small number of items and were based on self-report and teacher-report instruments, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study of emotional synchrony is complicated by the fact that emotions can have a positive or negative valence, and specifying the valence of emotions exchanged between parent and child has implications for children's adjustment. For example, research suggests that parent-child negative emotional reciprocity has particular significance for children's social competence relative to parent-child positive emotional reciprocity (Boyum & Parke, 1995;Carson & Parke, 1996). Although both positive and negative emotional synchrony are, strictly speaking, indices of a synchronous parent-child relationship (Harrist & Waugh, 2002), understanding their occurrence and patterning will aid in specifying the role that parent-child synchrony has in children's adjustment.…”
mentioning
confidence: 99%